Maternal and Perinatal Characterization of Patients with Preeclampsia and Eclampsia in a Health Center in Nioro du Sahel - Yuset Muñoz Ricart (Medisur)
Background: Preeclampsia is one of the most common pregnancy complications. It is often associated with low birth weight and high perinatal mortality. Objective: to characterize preeclampsia and eclampsia in pregnant women attending the Health Reference Center in Nioro du Sahel. Methods: a descriptive study involving 82 patients diagnosed with preeclampsia and eclampsia and 60 fetuses carried by them was conducted in the maternity department of the Health Reference Center in Nioro du Sahel from January to December 2008. Data was collected from emergency obstetric and neonatal records. Variables analyzed were: maternal age, method of delivery, fetal classification and neonatal weight. Results: pregnant women aged 15-20 years predominated. Vaginal delivery was performed in 41.46% of the patients. Neonatal survival was 63.33%, a high fetal mortality was observed. Fifty percent of neonates weighed 2650 grams or more. Conclusions: these results show a peculiar progression of preeclampsia and eclampsia in Nioro du Sahel village, since variables such as maternal age and method of delivery reflect values that differ from similar published studies.